Free Soil : The Election of 1848 - Rayback, Joseph G. (Book collections on Project MUSE., 1970)
The presidential election of 1848, known as the Free Soil election, marked the emergence of antislavery sentiment as a determining political force on a national scale. In this book Joseph G. Rayback provides the first comprehensive history of the campaign and the election, documenting his analysis with contemporary letters and newspaper accounts. The progress of the campaign is examined in light of the Free Soil movement: agitation for Free Soil candidates and platforms at the national conventions proved ineffective, and the nominations of Zachary Taylor and Lewis Cass completed the major part.